Perception of high school students about Bible classes - León, Vicente (2013)
This study aimed to characterize the perceptions of students from first to fourth through Adventist secondary schools Chilean Union have on the development of Bible classes. It also sought to establish whether there were differences in perception by gender and according to the religion of the participants. The research was conducted in 2012 in 24 high schools argues that the Adventist Church in Chile. The total number of participants was 4,941. The instrument used for the development of the study was created expressly and subjected to testing content validity and construct using factor analysis yielded three factors called "Interest in Bible class", "Methodology for Bible class" and "Evaluation is done in Bible class." The indicators of the instrument were evaluated on a scale: never, rarely, sometimes, often and always. The results showed that, of the 29 indicators that make up the instrument, only 8 of which are on average closer to the category "generally" and 21 said "sometimes". The Student t test showed that there are gender differences in the dimension "Interest in Bible class" and how they perceive the dimension "Assessment" made it ". The way ANOVA showed differences of perception in students according to their religious origin in the dimensions "Interest in Bible class" in the "Methodology that is used in it" and the "Evaluation is done in this class" . As a general conclusion may indicate that Bible class is a pending task that needs to be redesigned and greatly improved because the students in general not being perceived at an optimal level.